THE POTENCY OF BIOGAS PRODUCTION FROM HORSE MANURE AND TOFU LIQUID WASTE IN GEDONGSONGO - , DWI ASTUTI, ST, Dr. Ir. Sarto, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Horse manure and tofu liquid waste are present in abundant amount at Gedongsongo area. Horse manure may become the source of health and environment problem because it can spread disesase. While tofu liquid waste polluted the waterworks and water reservoir which well-marked by a dirty and unpleasant odor of water. The utilization of horse manure and tofu liquid waste as biogas raw material are expected to produce an optimum biogas production and may become a better solution to overcome the problem in Gedongsongo area and other area which have similar problem. The research done by placing samples into an anaerobic digester in temperature 32 o C for 30 days. The raw material used for this research are horse manure and tofu liquid waste in many concentration. The free variables of this reseach are the ratio between horse manure and tofu liquid waste and volatile solid. The pH, biogas volume, and methane concentration are then measured. The result of the research is that the optimum composition to obtain maximum volume of biogas production is horse manure and tofu liquid waste with mass ratio 0.6 : 0.4, which can produce 978.7667ml of biogas. While variation on mass ratio between horse manure and tofu liquid waste in the range of 0.5:0.5 to 0.7:0.3 does not give a significant difference on the methane composition produced. Nevertheless, the highest methane concentration obtained by horse manure and tofu liquid waste with mass ratio 0.6 : 0.4 at 28.81 % which can be reached on day 25. The low concentration of methane in the biogas produced still can be used as fuel by doing purification to get rid of the impurities.